DIDOMI POLEITEIAN ROMAION. TREŚĆ I ZAKRES NADANIA OBYWATELSTWA W CONSTITUTIO ANTONINIANA - Gumiela, Przemysław (Zeszyty Prawnicze, 2016)
DIDOMI POLEITEIAN ROMAION. DIDOMI POLEITEIAN ROMAION. THE CONTENT AND THE EXTENT OF THE CITIZENSHIP GRANT IN THE ‘CONSTITUTIO ANTONINIANA’ Summary In orbe Romano qui sunt ex constitutione imperatoris Antonini cives Romani effecti sunt – the mode, in which Ulpianus described the constitutio Antoniniana, does not reflect the importance of this act, the act by which nearly all inhabitants of the Imperium Romanum were granted Roman citizenship. Actually, the edict of Caracalla, released in 212 CE, was a revolutionary one. Nonetheless, due to brevity of antic testimonia, and particularly to the meagre condition of the papyrus Giessensis 42 (which carries the Greek version of the constitutio), numerous problems concerning the content and the extent of the citizenship grant remain yet unresolved. This paper aims at finding satisfactory answers to these questions. This attempt shall consist in a systematic analysis of the papyrus text read in the context of as many surviving sources as possible. A particular emphasis will be laid on the essence and the scope of the citizenship grant. This paper ignores, of necessity, several contextual questions, including those about the circumstances, motives and effects of the release. In fact, these problems are vast enough so as to be recognised separately.